Analysis of Factors Affecting Consumer Satisfaction and Their Impact on Green Product Consumer Loyalty - Ashur Harmadi; Misrofingah Misrofingah; Ratnawati Ratnawati; Edhie Budi Setiawan; Deni Apriansyah (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This study aims to examine and analyze the factors that influence consumer satisfaction and their impact on green product consumer loyalty. The population in this research is Starbucks consumers in the city of Jakarta, after that the illustrations are obtained by using the proportional random sampling method. This type of research is descriptive qualitative. The test was carried out by using question and answer questions to Starbucks customers. The results of the analysis support what is being monitored, so that it can be concluded that the respondents have been aware of what Starbucks has tried, which in this research examines the brand image of green product Starbucks with the assumption that service quality has a positive effect to customer happiness, brand views have a positive influence on customer happiness.